Students and Entrepreneurship: Effect of the Training - Salhi, Bassem; Boujelbene, Younes (Journal of Research in Educational Sciences; Vol 3 No 1 (2012): JRES, Volume III, Issue 1(5), 2012, 2012)
This paper is intended to explain the formation of entrepreneurial intentions of students from the Faculty of Sfax (Tunisia), after their participation in programs or courses on entrepreneurship. We are interested in understanding programs or courses in entrepreneurship in relation to a number of personal and contextual variables. On a theoretical level, it is based on psychosocial models such as the intent theory of planned behavior, based on the studies of Ajzen (1991), and the model of the entrepreneurial event of Shapero Entrepreneurship (Shapero and Sokol, 1982). According to these models, just considering starting a business brings about strong positive feelings, without thought for the reality of this as a desirable and feasible action. Model validation is based on a quantitative study, conducted on 120 students in third grade LMD, following the path of entrepreneurship. The choice of this sample is due to the fact that these students are just a few months away from entering the world of work. Our analysis shows that perceived desirability and feasibility are two prerequisites for the formation of entrepreneurial intentions. Indeed, the existence of an idea or project, and information retrieval, are the factors that contribute most outcomes of predictions on entrepreneurial intention. Our research will build an instrument that facilitates the analysis of the profiles for the recruitment of students wishing to take the entrepreneurial path.